Comparison of Real and Generated by MCNP Simulation Spectrums for Validation of Neutron Activation Calculations - Markopoulos, Angelos; Mavrikis, Dimitrios; Ntalla, Eleni; Ioannidou, Alexandra; Savidou, Anastasia (HNPS Advances in Nuclear Physics, 2022)
The objective for decommissioning planning, is to obtain a radiological understanding of the involved installation. The characterization at this stage could be carried out by means of: (a) neutron activation calculations based on reactor design and neutron flux; (b) dose rate measurements; (c) in-situ gamma spectrometry; (d) sampling for determination of the scaling factors in activated and contaminated components. Neutron activation calculations contains several uncertainties. These uncertainties are based on the input data - such as material data (composition and impurities), neutron flux and energy, nuclear data libraries - and on the methodology of the process and the simulation codes. Taking into consideration all these modeling uncertainties, this work is focused on the development of a technique for validation of the calculations. A non-destructive gamma spectrometry technique by using MCNP6 simulations is under development for interpretation of the resulting gamma-ray spectra of the radionuclides in activated components. In particular, a spectrum will be produced, based on the activities of the main radionuclides in the activated component and the results of MCNP6 simulations. This spectrum will be compared with the experimental spectrum. Furthermore, the radiological characterization of activated components, which appeared with surface contamination, is essential for the decision making process during decommissioning. The cutting techniques to be followed in order to reduce the production of secondary waste and limit the doses to personnel and the selection of decontamination techniques should be based on accurate determination of the radionuclides inside the material and/ or in the surface contamination. The proposed method could also be helpful in this case. The activities inside and on the surface of the components could be determined by comparing the experimental spectrum with that produced by MCNP6 simulations, using the arisen activities from the scaling factors and the dose rate measurements.